1999
DOI: 10.1890/0012-9658(1999)080[0998:rsoetc]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

REPRODUCTIVE SUCCESS OF EURASIAN TREECREEPERS,CERTHIA FAMILIARIS,LOWER IN TERRITORIES WITH WOOD ANTS

Abstract: Few studies have considered the effects of interspecific competition between distantly related taxa on the reproductive success of individuals. We compared the food supply, laying date, clutch size, and breeding success of a small double-brooded passerine bird, the Eurasian Treecreeper (Certhia familiaris) between territories with or without colonies of red wood ants (Formica rufa group) during four years. Both the wood ants and Eurasian Treecreepers forage on tree trunks and utilize the same food resources. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 58 publications
1
11
0
Order By: Relevance
“…Ants were unavailable to birds on no-ant branches, and if ants, in coffee systems, constitute a large part of bird diets, bird predation on other arthropods may have significantly increased where ants were excluded masking isolated effects of ants on arthropods. Alternatively, aggressive ants may deter bird feeding (Aho et al 1999;Haemig 1992Haemig , 1996. In this case, if ants significantly limit bird feeding when both predators are present, bird predation also would have increased and may have compensated for effects of ant removal, masking large effects of one or both ant species.…”
Section: Discussionmentioning
confidence: 99%
“…Ants were unavailable to birds on no-ant branches, and if ants, in coffee systems, constitute a large part of bird diets, bird predation on other arthropods may have significantly increased where ants were excluded masking isolated effects of ants on arthropods. Alternatively, aggressive ants may deter bird feeding (Aho et al 1999;Haemig 1992Haemig , 1996. In this case, if ants significantly limit bird feeding when both predators are present, bird predation also would have increased and may have compensated for effects of ant removal, masking large effects of one or both ant species.…”
Section: Discussionmentioning
confidence: 99%
“…In our nest-box population, the first eggs are laid in early April, when snow cover and night frosts still prevail in central Finland. Approximately 30% of the first breeders raise a second brood in June and July, which is usually reared by only the female (Aho et al 1999). Almost all juveniles migrate from the study area as a result of natal dispersal, whereas breeding birds are suggested to be sedentary (P. Suorsa and H. Hakkarainen, unpublished data).…”
Section: (A) Study Species and Breeding Datamentioning
confidence: 99%
“…We measured food abundance using vacuum cleaners on spruce and pine trunks during the period immediately after the fledging of the young treecreepers (Aho et al 1999). The trunk surface between the heights of 0.5 and 1.5 m was vacuumed in dry weather between 09.00 and 18.00.…”
Section: (D ) Monitoring Of the Provisioning Ratesmentioning
confidence: 99%
“…Savolainen & Vepsäläinen 1988, Niemelä et al 1992, Way & Khoo 1992, Karhu & Neuvonen 1998, Laakso & Setälä 2000, Martikainen et al 2000, Sipura 2002, Punttila et al 2004) and vertebrates (e.g. Haemig 1992, Aho et al 1999, Jäntti et al 2007) in all forest layers from the forest soil and floor up to the tree trunks and canopies. Further, they are important resource for both invertebrates and vertebrates (e.g.…”
Section: Introductionmentioning
confidence: 99%